Ripretinib in combination with tyrosine kinase inhibitor as a late-line treatment option for refractory gastrointestinal stromal tumors: two case reports and literature review - Zhang, Yefan; Huang, Zhen (Frontiers in Pharmacology, 2023)
Background: This case report presents two clinical cases of metastatic refractory gastrointestinal stromal tumor (GIST) with treatment history of 6–14 years. The follow-up treatment of both cases comprised ripretinib dose escalation and its combination with other tyrosine kinase inhibitors (TKIs). To the best of our knowledge, this is the first report that explored ripretinib combination therapy in the late-line treatment of GISTs. Case description: Case-1 represents a 57-year-old female patient who underwent surgical resection for retroperitoneal GIST in 2008. After tumor recurrence in 2009, imatinib was started with complete response for 8 years. Imatinib was followed by sunitinib and regorafenib treatment. In March 2021, due to progressive disease (PD), the patient started ripretinib (150 mg QD) and achieved partial response (PR). Six months later, the patient showed PD. Subsequently, ripretinib dose was increased (150 mg BID) followed by ripretinib (100 mg QD) and imatinib (200 mg QD) combination. CT performed in February 2022 revealed stable lesions with internal visible necrosis. Combination therapy achieved stable disease (SD) for 7 months. On further follow-up in July 2022, the patient showed PD and died in September 2022. Case-2 represents a 73-year-old female patient diagnosed with unresectable duodenal GIST with liver, lung, and lymph node metastasis in 2016. After treatment with imatinib, followed by sunitinib, regorafenib, and imatinib rechallenge, ripretinib (150 mg QD) was administered in May 2021, and SD was achieved. Ripretinib dose was increased (200 mg QD) due to PD in December 2021. The tumor showed heterogeneous manifestations, with overall size increase and regression in right posterior lobe. In February 2022, ripretinib (150 mg) plus sunitinib (25 mg) QD was commenced. On follow-up in April 2022, the patient showed slightly improved symptoms with stable hematologic parameters. Combination therapy achieved SD for 5 months and the patient showed PD in July 2022 and discontinued the treatment later. The patient was in poor general condition and was receiving nutritional therapy until last follow-up in October 2022. Conclusion: This case report provides evidence that combination therapy of ripretinib with other TKIs could be an effective late-line treatment option for refractory GIST patients.